Canistel Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
Revised! HS-1049, a 7-page fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides homeowners with a basic reference for growing canistel in the home landscape. Tables include varieties in Florida, cultural practices by month, fertilizer program and nutritional values. Published by the UF Department of Horticultural Sciences, October 2006.